Effect of potassium fertilizer application on total phenolic level, flavonoids, and the antioxidant activity of the Purslane (Portulaca oleracea) - Rafiqi, A.; Yodi, G.; Mustika, T. M.; Rahmah, S. F.; Hutabarat, E. S. O.; Marliani, N.; Aisyah, S. I.; Kurniatin, P. A.; Galingging, R. Y.; Nurcholis, W. (International Journal of Agricultural Technology, 2025)
The study investigated the impact of K fertilizer on the antioxidant properties of purslane (Portulaca oleracea L.) ethanol extract. The total phenolic content was measured using the Folin-Ciocalteu method with gallic acid standards, peaked in the F3 treatment (0.15 g potassium per plant) at 1.4929 mg GAE/g. Total flavonoid levels, assessed with quercetin as the standard, were highest in the F3 treatment at 0.1602 mg QE/g. Antioxidant activity was evaluated through FRAP, CUPRAC, and ABTS methods, with Trolox standards, revealing the highest values of 3.7644 μmol TE/g in the control (F0), 2.1197 μmol TE/g in F2 (0.1 g potassium per plant), and 6.4251 μmol TE/g in F2, respectively. Potassium fertilizers were significantly increased the total phenolic and flavonoid content, particularly in the F3 treatment, which applied 0.15 grams of fertilizer per sample over nine repetitions. Despite this increase, the highest antioxidant activity was not observed in the F3 treatment, due to variables such as sample storage time, dilution, and pre-test handling. The findings highlighted a complex relationship between potassium fertilization and antioxidant activity in purslane, suggesting potential variables influencing antioxidant outcomes beyond phenolic and flavonoid content.